The Role of Brand Trust and Social Media Engagement in Driving Purchase Intention among Indonesian SMEs - Amin, Muhammad; Hasanuddin, Muhammad; Supiyandi (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The study investigates the influence of digital marketing strategies—social media engagement, online advertising, and brand trust—on consumer purchase intention in Indonesia’s SME sector. Using a quantitative design, data were collected from 150 SME consumers via structured online questionnaires and analyzed through multiple regression using SPSS 26.0. The model explained 65.7% of the variance in purchase intention, indicating a strong predictive capacity. Results revealed that all three independent variables significantly affect purchase intention, with brand trust emerging as the most influential predictor. The findings underscore that trust, transparency, and interactive engagement are essential in transforming digital exposure into purchasing behavior. Moreover, they highlight the necessity for SMEs to integrate ethical governance and culturally aligned digital communication to strengthen customer relationships and brand credibility. This research contributes to the literature by contextualizing digital marketing effectiveness within an emerging economy, offering theoretical insights and practical recommendations for designing trust-based digital strategies. The study’s implications encourage further exploration of mediating and moderating factors, such as consumer satisfaction and perceived risk, to deepen understanding of behavioral mechanisms in digital markets.